IDENTIFICATION OF LEARNING DIFFICULTIES IN JUNIOR HIGH SCHOOL PHYSICS IN LANGKAT REGENCY - Irham Ramadhani; Ratna Tanjung (IPER (Indonesian Physics Education Research), 2020)
This research was conducted to map the factors that became the source of student learning difficulties in terms of the learning process and the difficulties experienced in solving Newton's style and law problems. The population of this descriptive study was all students of class VIII in Langkat Regency, while the schools that were the samples in this were students of class VIII in three schools, namely SMP Negeri 2 Stabat, SMP Seri Langkat, and SMP Negeri 3 Satu Atap. Data collection in this study was conducted using student questionnaire instruments, teacher questionnaires, learning activity observation sheets, student activity assessment sheets and essay questions. The analysis of the research results found that the factors that influence the learning difficulties of junior high school students in Langkat Regency are the weak of Utilization of Learning Resources / Learning Media, the inadequate learning which can trigger and maintain student engagement and the low ability of students to solve problems coherently. Keywords: Learning Difficulties, Descriptive Study, Observation Sheet